Coincidence theory and KKM type maps - O'REGAN, Donal (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this paper we present a variety of coincidence results for classes of maps defined on Hausdor topological vector spaces. Our theory is based on fixed point theory in the literature. Mathematics Subject Classification (2010): 47H10, 54H25. Received 17 January 2024; Accepted 25 June 2024.